A Sixteen-year Decline in Dissolved Oxygen in the Central California Current - Alice S. Ren (Nature Portfolio, 2018)
Abstract A potential consequence of climate change is global decrease in dissolved oxygen at depth in the oceans due to changes in the balance of ventilation, mixing, respiration, and photosynthesis. We present hydrographic cruise observations of declining dissolved oxygen collected along CalCOFI Line 66.7 (Line 67) off of Monterey Bay, in the Central California Current region, and investigate likely mechanisms. Between 1998 and 2013, dissolved oxygen decreased at the mean rate of 1.92 µmol kg−1 year−1 on σθ 26.6–26.8 kg m−3 isopycnals (250–400 m), translating to a 40% decline from initial concentrations. Two cores of elevated dissolved oxygen decline at 130 and 240 km from shore, which we suggest are a California Undercurrent and a California Current signal respectively, occurred on σθ ranges of 26.0–26.8 kg m−3 (100–400 m). A box model suggests that small annual changes in dissolved oxygen in source regions are sufficient to be the primary driver of the mid-depth declines. Variation in dissolved oxygen at the bottom of the surface mixed layer suggests that there is also a signal of increased local remineralization.